Emerging Therapies in Cutaneous Lupus Erythematosus - Sprow, Grant; Dan, Joshua; Merola, Joseph F.; Werth, Victoria P. (Frontiers in Medicine, 2022)
Cutaneous lupus erythematosus (CLE) is an autoimmune disease that can occur with or without underlying systemic lupus erythematosus (SLE) and often has a profoundly negative impact on patient quality of life. There is substantial need for new and more effective therapies to treat CLE. CLE has a multifactorial pathogenesis that involves several key immune cells and pathways, including abnormalities in innate (e.g., type 1 interferon pathways) and adaptive immune responses (e.g., B and T cell autoreactivity), presenting multiple opportunities for more targeted therapies that do not require immunosuppression. Here we review several emerging therapies and their efficacy in CLE. Anifrolumab and belimumab have both been approved for the treatment of SLE in recent years, and clinical trial evidence suggests some forms of CLE may improve with these agents. Therapies currently in development that are being evaluated with CLE-specific outcome measures include BIIB059 and VIB7734, which target plasmacytoid dendritic cells (pDCs), and iberdomide, a cereblon modulator. These novel therapies all have previously demonstrated clinical benefit in some forms of CLE. Other therapies which target molecules believed to play a role in CLE pathogenesis, such as janus kinases (JAKs), spleen tyrosine kinase (SYK), interferon γ (IFNγ), IL-12, and IL-23, have been evaluated in lupus clinical trials with skin-specific outcomes but failed to meet their primary endpoints.